Assisted reproductive technology and multiple pregnancy in Malta — A population based study. (June 2021) - Grech, Victor; Gatt, Miriam
Abstract: Introduction: Assisted reproductive technology (ART) is increasingly used to overcome growing rates of infertility and subfertility. Perinatal and maternal morbidity and mortality are elevated in ART conceptions even in vaginally delivered singletons. Malta is a small archipelago with comprehensive national data. This study was carried out in order to investigate ART rates in Maltese deliveries for 2000–2019 inclusive. Methods: Anonymous data was obtained from the Malta National Obstetric Information System (NOIS). For this study all ART methods were aggregated into one group. Deliveries refer to single pregnancies. A p value ≤0.05 was taken to represent statistically significance. Results: This study analysed 82, 356 deliveries over the period with overall 2% ART. There was a significant rising trend in all deliveries (ART plus non-ART) with time ( p  = 0.012). Of these, 1262 were twin deliveries (18% ART) and 56 were triplet deliveries (66% ART). Multiple deliveries (ART plus non-ART) also rose significantly ( p  = 0. 00035). The proportion of ART deliveries rose significantly overall and individually, for singletons (3.4–4.6%) since 2018, and over a quarter of such deliveries since 2013 for twin and further multiples. Discussion: The Maltese rate of twins and triplets plateaued before reaching the peaks experienced by other countries and it may be that more infertile couples were and are only having one embryo transferred. In smaller countries with only one neonatal unit, ART services should strive to produce a smooth throughput so as to minimize surges and strains on downstream neonatal services which may have deleterious effects on outcomes, especially neonatal. Highlights: Assisted reproductive technology (ART) is increasingly utilized. ART is associated with multiple pregnancy and perinatal and maternal morbidity and mortality. The Maltese rate of ART is similar to other countries, with less multiple pregnancies. In small countries with one hospital, ART must be careful not to overwhelm neonatal services.